Implementation of Diagnostic Assessment in Learning Mahārah Qirā’ah Based on Technological Pedagogical and Content Knowledge Al-Kautsar Bintaro Middle School: Tatbīq Attaqwīm Attasykhīshī fī Ta’līmī Mahārah Qirāah alqāim ‘ala Alma’rifat Attarbawiyyah Attiknulujiyyah wa Almuhtaawa Alma’ruf (TPACK) fī Madrasati Alkautsar Alibtidāiyyah Alislāmiyyah Bintaro - Alya Putri Septianti; Ubaid Ridlo; Raswan (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2024)
The development of ICT (Information, communication, & technology) requires teachers to innovate and align themselves with technological developments, diagnostic assessment is vital in identifying students initial abilities, strengths, and weaknesses in Arabic text reading skills. With the integration of TPACK, teachers can utilize technology to design assessment instruments that are more effective, interactive, and relevant to students needs, as well as develop pedagogical approaches that match the characteristics of the content. This research aims to provide a deeper understanding of how technology, if appropriately integrated with pedagogical and language content understanding, can effectively improve Arabic language teaching and learning, particularly in the diagnostic assessment of mahārah qirā’ah.  The research method used is descriptive qualitative. The research data sources are divided into two sources: the first source of literary data and field data sources. Data were collected through classroom observations, interviews, and analysis of student assessment documents. The results showed that TPACK-based diagnostic assessment helped teachers map students abilities more thoroughly. Technology allows the presentation of more varied and exciting assessments, thus increasing student motivation in learning. In addition, integrating technology, pedagogy, and content makes it easier for teachers to design more targeted and practical knowledge. Keywords: Diagnostic Assessment, Mahārah Qirā’ah, TPACK